Systemic and vascular effects of circulating diesel exhaust particulate matter. (November 2013) - Bai, Ni; van Eeden, Stephan F.
Abstract Objective: Numerous studies have found an association between transiently increased particulate matter air pollution and acute adverse cardiovascular health effects; however, the mechanisms underlying these effects are not clear. Translocation of ultra-fine ambient particulate matter has been proposed to play a key role in these acute side effects. This study was designed to determine the contribution of circulating (translocated) diesel exhaust particles (DEPs) to the systemic and vascular effects. Methods: C57 mice (10-week) received intravenous DEPs via tail vein injection. Following 1-h post-injection, inflammatory cytokines (IL-1β, IL-6 and TNF-α), peripheral blood cell counts, band cell counts, aortic endothelial function and vascular constriction were assessed. Thoracic aortae were isolated, and endothelial function was examined by measuring acetylcholine (ACh) and sodium nitroprusside (SNP)-stimulated vascular relaxation using a wire myograph. In addition, phenylephrine (PE)-stimulated vasoconstriction was also measured. The amount of DEPs deposited and trapped in tissues (the spleen, liver, lungs and heart) were quantified. Results: Acute systemic DEP exposure caused a significant increase in TNF-α, peripheral neutrophil and band cell counts. ACh and SNP-induced relaxation were not affected by acute systemic DEP exposure, neither was PE-stimulated constriction. There was a significantly increased DEP deposition in the spleen as well as in the liver. No significantly increased DEPs were detected in the lung and heart. Conclusion: Here we show that circulating DEPs induce a systemic response characterized by increased TNF-α, peripheral granulocytes, but does not impact endothelial function. Our study also suggests that circulating particles are rapidly removed from the circulation and predominantly sequestered in the spleen and liver.